Spectacularization of political activism: Subject matter and social effect - Khoma, Nataliia; Kozma, Vasyl (The Greek Review of Social Research, 2022)
Political actionism can be defined as a type of political participation that manifests through various spectacular forms of sociopolitical activism and has become increasingly prevalent in contemporary politics. This paper aims to show the significance and effectiveness of political actionism as a modern form of political activism. It will be argued that political actionism is capable of reshaping political processes through theatrical representations, specifically the play format, and other forms of entertainment. Furthermore, evidence will be presented of its increasing importance in the information society. The different possible functions and directions of political actionism in postmodern politics will also be outlined and the role of symbolization, visualization, provocation, and carnivalization in political actionism will be elucidated. Departures from the previous system of political activism will be exemplified through a discussion of political performances, happenings, and art installations, three essential forms of political actionism, and emphasis will be laid on the varying role and social significance of political actionism depending on the political regime of a particular state. Finally, a comprehensive typology of actionism will be proposed.